Factors Contributing to Medication Adherence in Patients with a Chronic Condition: A Scoping Review of Qualitative Research - Kirsi Kvarnström; Aleksi Westerholm; Marja Airaksinen; Helena Liira (MDPI AG, 2021)
Introduction: Medication adherence continues to be a significant challenge in healthcare, and there is a shortage of effective interventions in this area. This scoping review studied the patient-related factors of medication adherence. Methods: We searched Medline Ovid, Scopus, and Cochrane Library from January 2009 to June 2021 to find the most recent original qualitative studies or systematic reviews that addressed the patient-related factors of medication adherence in treating chronic conditions. We used the PRISMA-ScR checklist to ensure the quality of the study. Results: The initial search revealed 4404 studies, of which we included 89 qualitative studies in the scoping review. We inductively organized the patient-related factors causing barriers, as well as the facilitators to medication adherence. The studies more often dealt with barriers than facilitators. We classified the factors as patient-specific, illness-specific, medication-related, healthcare and system-related, sociocultural, as well as logistical and financial factors. Information and knowledge of diseases and their treatment, communication, trust in patient-provider relationships, support, and adequate resources appeared to be the critical facilitators in medication adherence from the patient perspective. Discussion and conclusions: Patients are willing to discuss their concerns about medications. Better communication and better information on medicines appear to be among the critical factors for patients. The findings of this scoping review may help those who plan further interventions to improve medication adherence.